Medicine in spine exercise (MiSpEx) for nonspecific low back pain patients: study protocol for a multicentre, single-blind randomized controlled trial. Issue 1 (December 2016) - Niederer, Daniel; Vogt, Lutz; Wippert, Pia-Maria; Puschmann, Anne-Katrin; Pfeifer, Ann-Christin; Schiltenwolf, Marcus; Banzer, Winfried; Mayer, Frank
Abstract Background Arising from the relevance of sensorimotor training in the therapy of nonspecific low back pain patients and from the value of individualized therapy, the present trial aims to test the feasibility and efficacy of individualized sensorimotor training interventions in patients suffering from nonspecific low back pain. Methods and study design A multicentre, single-blind two-armed randomized controlled trial to evaluate the effects of a 12-week (3 weeks supervised centre-based and 9 weeks home-based) individualized sensorimotor exercise program is performed. The control group stays inactive during this period. Outcomes are pain, and pain-associated function as well as motor function in adults with nonspecific low back pain. Each participant is scheduled to five measurement dates: baseline (M1), following centre-based training (M2), following home-based training (M3) and at two follow-up time points 6 months (M4) and 12 months (M5) after M1. All investigations and the assessment of the primary and secondary outcomes are performed in a standardized order: questionnaires – clinical examination – biomechanics (motor function). Subsequent statistical procedures are executed after the examination of underlying assumptions for parametric or rather non-parametric testing. Discussion The results and practical relevance of the study will be of clinical and practical relevance not only for researchers and policy makers but also for the general population suffering from nonspecific low back pain. Trial registration Identification number DRKS00010129. German Clinical Trial registered on 3 March 2016.